Analisis Tindak Tutur Lokusi dan Ilokusi pada Caption Instagram Jerome Polin - Christina Margaretha Naibaho; Harlen Simanjuntak; Tigor Sitohang (Neolectura, 2022)
Speech acts are actions that involve parties who can interact well, which results in actions that can affect the interlocutor. Nowadays, various information, works, and ideas can be seen on social media. Social media is a place for users to interact socially, share, communicate, and work. It certainly allows a user to communicate with idols such as singers, actresses, writers, and comedians. Jerome Polin has 6.9 million followers on social media Instagram. The purpose of this study is to describe the form of locutionary and illocutionary speech acts and their functions on the Jerome Polin Instagram account. This study used descriptive qualitative method. The source of the data in this study is the caption on Jerome Polin's Instagram account in December to April. The data collection technique was carried out by the documentation method. The results of the study found 121 data which are locutionary speech acts and 87 data which are illocutionary speech acts. Locutionary and illocutionary speech acts are used as a place to show what the speaker wants to share with his followers on Instagram, starting from informing, telling, being grateful, thanking, happy, sad, ordering, asking, and offering. This research is expected to develop the field of pragmatics and the public can understand the meaning of locutionary and illocutionary speech acts that will be useful in life.